Transition to Online Education during the COVID-19 Pandemic: Impact of Changes in Alcohol Consumption and Experiencing Hangovers on Academic Functioning - Agnese Merlo (MDPI AG, 2021)
In the Netherlands, the 2019 coronavirus (COVID-19) pandemic had a significant impact on daily life, with two extensive lockdowns enforced to combat the spread of the SARS-CoV-2 virus. These measures included the closure of bars and restaurants, and the transition from face-to-face to online education. A survey was conducted among Dutch pharmacy students and PhD-candidates to investigate the impact of COVID-19 lockdown on alcohol consumption, hangovers, and academic functioning. The analysis revealed a significant reduction in both quantity and frequency of alcohol consumption during the COVID-19 lockdown periods. This was accompanied with a significant reduction in hangover frequency and lower hangover severity during COVID-19 lockdown periods. The distribution of scores on academic performance showed great variability between respondents: while some participants reported impairment, others reported improved performance during the COVID-19 pandemic, or no change. Women reported that significantly more time investment was associated with maintaining these performance levels. Consistent among participants was the notion of reduced interactions with teachers and other students. Participants who reported more hangovers and most severe hangovers before COVID-19 benefited from the lockdown periods in terms of improved academic performance. Positive correlations were found between study grades/output and both the frequency and severity of hangovers experienced before COVID-19, suggesting that heavier drinkers, in particular, improved academic performance during the lockdown periods. In conclusion, COVID-19 lockdowns were associated with a significant reduction in both alcohol consumption and experiencing hangovers, which was, among heavier drinkers particularly, associated with significantly improved academic functioning.